Viral Marketing Concept and Viral Marketing Development on Consumer Buying Approach - Lucky Radi Rinandiyana; Tine Badriatin; Asep Saepudin (Almana : Jurnal Manajemen dan Bisnis, 2022)
Viral Marketing is one of the current marketing promotion techniques. Viral Marketing is a type of marketing that uses social media to achieve certain marketing goals. Marketing technology is achieved by establishing the communication process chain itself. The key to viral marketing is to attract website visitors and refer them to others they believe will be interested which will increase consumer buying. Therefore this research also aims to help marketing through viral marketing which will be very effective to be able to telling the public about the products being marketed. Qualitative descriptive methods were used, and the results obtained were that spreading social marketing through viral marketing was very effective in informing the public about the products being marketed, because the process of disseminating information through Instagram social media accounts was very fast and did not care about the time or distance of production. one marketing through viral development. The main purpose of viral marketing is to spread promotions on social media, allowing the general public to not only be a passive observer but also to participate in marketing and react to something to adopt a more positive attitude.